Cover Feature: Unusual Lipid A from a Cold‐Adapted Bacterium: Detailed Structural Characterization (ChemBioChem 18/2017). (1st September 2017) - Casillo, Angela; Ziaco, Marcello; Lindner, Buko; Parrilli, Ermenegilda; Schwudke, Dominik; Holgado, Aurora; Verstrepen, Lynn; Sannino, Filomena; Beyaert, Rudi; Lanzetta, Rosa; Tutino, Maria Luisa; Corsaro, Maria Michela
Abstract : The back cover picture shows one of the strategies for counteracting the cold stress adopted from the Arctic isolate Colwellia psychrerythraea 34H. Bacteria thriving in cold habitats have developed various mechanisms to avoid the cells freezing. Some of these strategies involve outer‐membrane (OM) molecules such as lipopolysaccharides. These molecules are embedded in the OM through their glycolipid portion and, together with phospholipids, are devoted to maintaining the fluidity of the membrane. We have completely characterised the lipid A portion of the lipopolysaccharide from Colwellia, a contribution to the elucidation of the structure–function relationship for these molecules isolated from psychrophiles. More information can be found in the full paper by A. Casillo, M. M. Corsaro et al. onpage 1845 in Issue 18, 2017 (DOI:10.1002/cbic.201700287 ).